The Consequences of Taliban’s Resurgence for Iranian Economic Diplomacy in Afghanistan - Hamed Askari Kermani; Arash Saffar (رهیافتهای سیاسی و بین المللی)
During Coalition forces in Afghanistan, Iran managed to overcome its traditional rivals and become the largest exporter of goods to this country. Therefore, the Taliban's presence in Kabul is essential for Iran not just due to political and security issues but also because of economic reasons. One way to understand and analyze the foundations of Iran's success in this particular area during the coalition forces, and also the consequences of the Taliban's hegemony in Afghanistan at the moment, is economic diplomacy. This article introduces and suggests an economic diplomacy approach in which the state and its strategic interests are fundamental elements for the analysis. Then, it will try to put Iran's economic achievements in Afghanistan during the last two decades in that context and argue based on that approach the consequences of a Taliban-controlled Afghanistan for those achievements. The article explains that uncertainties, new foreign players, and a decline in the revenue of Afghanistan's government and people are the main challenges for Iran's economic diplomacy in Afghanistan.